Switching transcription with bacterial RNA polymerase through photocaging, photorelease and phosphorylation reactions in the major groove of DNA - Vaníková, Zuzana; Janoušková, Martina; Kambová, Milada; Krásný, Libor; Hocek, Michal (Chemical science, 2019)
We report proof of principle biomimetic switching of transcription in vitro through non-natural chemical reactions in the major groove of DNA templates. Photocaged DNA templates containing nitrobenzyl-protected 5-hydroxymethyluracil or - cytosine permitted no transcription with E. coli RNA polymerase (OFF state). Their irradiation with 400 nm light resulted in DNA templates containing hydroxymethylpyrimidines, which switched transcription ON with a higher yield (250-350%) compared to non-modified DNA. Phosphorylation of templates containing 5-hydroxymethyluracil (but not 5-hydroxymethylcytosine) then turned transcription OFF again. It is the first step towards artificial bioorthogonal chemical epigenetics.